The The Appeal of Halal Labels: How much Influence Does It Have on Purchasing Decisions? A Quantitative Study of Packaged Food and Beverages in a Muslim-Majority Market - Zana Zein Hardimanto (Jurnal Ilmiah Ekonomi Islam, 2025)
Abstract This study aims to examine the extent to which halal labeling on packaged food and beverages influences consumer purchasing decisions. A quantitative approach was employed, utilizing both primary and secondary data sources. The research involved 260 respondents selected through purposive sampling. Data analysis was conducted using simple linear regression. The result show that the halal labeling variable has a positive and significant effect on purchasing decisions, with a statistical significance value of less than 0.05. These findings indicate that the halal labeling variable on packaged food and beverage has a positive and significant inluence on purchasing decisions, as it shows an empirical probability or statisticcal significance value of less than 0.05. In economic terms, this reflects the responsiveness of consumers labeling to to labeling, especially those those guided by religious values. In predominanlty muslim societies, such as Surakarta trust and adherence to religious principles are crucial factors influencing product selection and purchasing behaviour. The study confirms that enchanging halal labeling can strengthen consumer confidence and drive higher purchasing in muslim majority markets. Keywords: halal label, purchasing decision, consumer behavior, religious values, packaged food and beverages